Resonance suppression and quality improvement control strategy for a three-phase grid-connected voltage-source inverter under weak grid conditions - Zhang, Zhi; Li, Yiyun; Zhong, Caomao; Zhang, Zhaoyun (Frontiers in Energy Research, 2023)
The three-phase voltage-source grid-connected inverters suffer from grid-connected current quality problems due to system resonance caused by the under-damping characteristics of the filter and grid impedance, on the one hand, and the grid-connected current distortion caused by the high content of low harmonics in the grid voltage, on the other hand. To resolve this problem, a current quality improvement control strategy, combining capacitor-current feedforward active damping and harmonic virtual impedance reshaping, is proposed by analyzing the mechanisms of system resonance and grid-connected current distortion. In addition, the proposed control strategy allows determining the virtual impedance parameters by using the root locus method, so as to achieve the purpose of improving the output grid-connected current quality of the three-phase voltage-source grid-connected inverter under weak grid conditions. Finally, the correctness and effectiveness of the proposed control strategy are verified by simulation and experiment.